A guide to a new short course to promote interest and engagement in psychiatry in medical students. (August 2015) - Langley, Matthew; Lomas, Benjamin; Schofield, Zena; Doody, Gillian
Summary: This article describes a new course for preclinical medical undergraduates designed to promote interest and engagement in psychiatry. The course employed a range of innovative teaching techniques alongside ward visits to provide students with early clinical experience. Unusually, assessment for the course involved the production of creative works as well as reflective writing about students' experiences. We collected a variety of feedback from participants showing that they found the course enjoyable and educational. We conclude that, overall, the course had a positive effect on student perceptions of psychiatry.